Efficient and strategy‐proof allocation mechanisms in economies with many goods. Issue 3 (22nd September 2017) - Momi, Takeshi
Abstract : In this paper, we show that in pure exchange economies where the number of goods equals or exceeds the number of agents, any Pareto‐efficient and strategy‐proof allocation mechanism always allocates the total endowment to some single agent even if the receivers vary.